(untitled) (Bangladesh Journal of Medical Science, 2024)
Objectives Axillary lymph node status is the most important prognostic factor in breast cancer patients.: This study was carried out to evaluate the diagnostic accuracy of FDG-PET/CT as a noninvasive technique and intraoperative frozen biopsy of sentinel lymphadenectomy (SLNB) in detecting axillary lymph node metastasis. Materials and Methods This study was carried out retrospectively on 44 patients diagnosed with breast cancer, who underwent preoperative FDGPET/ CT imaging and intraoperative SLNB, at the General Surgery Clinic of Istanbul Medeniyet University Göztepe Training and Research Hospital. The axilla was clinically negative in all patients. Preopative FDG-PET/CT imaging and intraoperative SLNB were performed. FDG-PET/CT results were compared with the histopathological results of SLNB and axillary lymph node dissection (ALND). Results According to the pathology results of axillary dissection, metastatic nodes were detected in 22 of 44 cases, and FDG-PET/ CT imaging gave false-negative results in 10. The number of false negative cases of SLNB was 3; Axillary involvement was detected as a result of pathology in one of them, while the others were evaluated as skip metastases. The sensitivity of SLNB and FDG-PET/CT imaging was measured as 86.3% and 54.5%. The specificity values were 95.4% and 100%. FDG-PET/CT imaging has low sensitivity; specificity and positive predictive value were at acceptable levels Conclusion: The sensitivity of FDG-PET/CT imaging is low in detecting axillary involvement, and SLNB is needed in those with negative axillary involvement in FDG-PET/ CT imaging. In our study, SLNB examination was superior to FDG-PET/CT imaging in detecting axillary nodal status. Bangladesh Journal of Medical Science Vol. 23 No. 04 October’24 Page : 1083-1094